Cooling and Eutrophication of Southern Chilean Lakes - Vergara-Egert, P (Elsevier, 2016)
Understanding the impacts of global warming and human-disturbances on lakes is required for implementing management strategies aimed at mitigating the decline of the quality and availability of water for humans. We assessed temporal trends in water parameters, and the contribution of land use to the eutrophication of the largest lakes of central-southern Chile. The mean values of water parameters varied seasonally, with lakes Chapo and Caburgua exhibiting lower pH, temperature, and N/P ratio values. Over the assessed period (19years), we found a temporal reduction in water conductivity and temperature of the lakes. The concentration of NO3-_N, PO43--P and dissolved oxygen increased in all the lakes, but pH increased in eight out of the ten lakes. The negative temporal trend in temperature was more pronounced as the depth level increased. Lakes whose basins had a higher percentage of forest plantation and urban areas had larger values of Chlorophyll a and pH, as well as, smaller values of dissolved oxygen. Lakes whose basins included larger percentages of native forest had smaller nutrient (NO3-_N, PO43--P) concentrations. Our findings suggest that decreased rainfall in central-southern Chile due to climate change may cause a decrease of particulate material that is carried by tributaries into the lakes. The observed temporal decrease in temperature, especially at the deeper levels, may be explained by the rapid melting of glaciers. Although the studied lakes are classified as oligotrophic, deforestation and expansion of urban areas around the lakes have led to increased nutrient input, thus accelerating their eutrophication. © 2015 Elsevier B.V.